Lead pollution and its sources, transmission routes, and health and environmental impacts (comprehensive review) (Journal of the College of Basic Education, 2026)
This research aims to study industrial lead emissions and reveal their health and environmental effects by studying their emission sources, their transport mechanisms in the environment, and their effects on humans and ecosystems. The results showed that lead is one of the most dangerous heavy metals that accumulate in the environment, as it is transported through air, water, and soil. Then it enters food chains, causing serious health disorders, including damage to the nervous system, anemia, and delayed mental development in children. The study also showed that heavy industries, battery recycling, and metallurgical processes are among the most prominent sources of emissions. The accumulation of lead in soil and water leads to a decline in fertility and a decrease in biodiversity. The research findings underscore the need for effective strategies to reduce emissions. This includes developing industrial technologies, strengthening regulatory legislation, improving waste management, along intensifying monitoring programs and raising community awareness. The research concludes that addressing lead pollution requires an integration of scientific and technical efforts to ensure the protection of human health and the environment.